Global Investment Costs for Coastal Defense through the 21st Century - Nicholls, Robert John (World Bank E-Library Archive, 2019)
Sea-level rise threatens low-lying areas around the world's coasts with increased coastal flooding during storms. One response to this challenge is to build or upgrade coastal flood defenses. This report examines the potential investment costs of such an adaptation strategy applied globally over the 21st century for sea-level rise scenarios consistent with three Representative Concentration Pathways and 3 Shared Socioeconomic Pathways. For all the protection models considered, much less than half of the world's coast is protected. The total defense costs are significantly higher than earlier estimates, amounting to as much as USD 18.3 trillion. With cost-benefit analysis, there are large uncertainties and empirical observations of protection standards are limited. Hence, the estimates should be considered as indicative, and this remains an important topic for future research. Further, building defenses is not a one-off capital investment. Over the 21st century, the cost of a comprehensive protection strategy is dominated by maintenance costs in all the cases considered in this report. This indicates that in addition to capital investment, the development of appropriate institutions and governance mechanisms to deliver maintenance, as well as the necessary funding streams, are essential for such a protection-based adaptation strategy to be effective